(untitled) (The Research of Medical Science Review, 2025)
Background: The assessment of enlarged perivascular spaces (ePVS) and diffusivity along the perivascular spaces (DTI-ALPS) has gained significant attention as emerging biomarkers in neurological disease. These imaging markers provide insights into the glymphatic system, which plays a critical role in brain waste clearance and neurovascular health. Alterations in ePVS and DTI-ALPS have been linked to various conditions such as Alzheimer’s disease, stroke, and hypertension, highlighting their potential for early diagnosis and monitoring of disease progression. Objective: To Assess Enlarged Perivascular Spaces and Index for Diffusivity along the Perivascular Spaces as Emerging Neuroimaging Biomarker of Neurological Disease. Methodology: This cross-sectional study was conducted at National Hospital, Lahore from July 2024 to December 2024. A sample size of 60 patients, aged between 18-65 years, with suspected neurological disorders was selected, excluding those with a history of brain trauma or prior treatment for malignancy. All patients underwent MRI using a 1.5T MRI machine, including T1, T2, and diffusion tensor imaging (DTI). Statistical analysis was performed using SPSS version 25, with cross-tabulation and T-test applied to compare the findings of DTI and conventional MRI sequences. Results: The study included 56 patients, with 38 (67.9%) males and 18 (32.1%) females. Enlarged perivascular spaces (EPVS) were most commonly found in the basal ganglia (26.8%) and centrum semi ovale (25.0%), with severity increasing across grades 1–4. Greater EPVS burden correlated significantly (p < 0.001) with higher apparent diffusion coefficient (ADC) values, indicating microstructural brain changes. Patients with severe EPVS showed higher rates of motor (39.3%) and cognitive impairment (60.7%), with MMSE scores declining as EPVS severity increased. The strong association between EPVS, ADC values, and neurological dysfunction supports diffusion indices as a reliable tool for assessing neurodegenerative changes. Conclusion: The study concluded that enlarged perivascular spaces (ePVS) and diffusion indices were valuable neuroimaging biomarkers for assessing neurological disease severity. Significant correlations between neurological disorder type, MMSE scores, disease severity, and ADC values supported the role of glymphatic dysfunction in neurodegeneration. The findings highlighted the potential of diffusion-based imaging for early disease detection and monitoring cognitive decline, emphasizing its clinical relevance in neurological assessment.